PREPARATION AND CHARACTERIZATION OF NOVEL LOXOPROFEN-LOADED SOLID LIPID NANOPARTICLES - HASAN, TABAREK KHALID; ABDUL-HASAN, MAZIN THAMIR (International Journal of Applied Pharmaceutics, 2025)
Objective: solid lipid nanoparticles (SLNs) exhibit many beneficial characteristics in the formulation of drug delivery systems. Loxoprofen (LX) is a non-steroidal anti-inflammatory drug (NSAID). This work aims to prepare and evaluate novel LX-loaded SLNs (LX-SLNs). Methods: Experimental formulas were developed using Design-Expert 13. The Formulas were prepared via hot emulsification followed by probe ultrasonication then evaluated for their particle size, polydispersity index (PDI) and entrapment efficiency (EE%). The optimum formula was selected and lyophilized for further testing of fourier transformed-infrared spectroscopy (FTIR), powder x-ray diffraction (PXRD), and field emission scanning electronic microscopy (FE-SEM). In vitro release studies were conducted on pure LX and five formulas with varying lipid amounts and types. Results: The optimization LX-SLNs formulations was performed using Design-Expert 13, with run 13 identified as the optimal formulation. This formulation, containing glyceryl monostearate (GMS) and poloxamer 407 (PX407), showed the best overall results in terms of particle size (70±4 nm), PDI (0.02±0.001), and EE% (88.07%±0.8). The release studies demonstrated sustained release behavior, with a decrease in the release rate as the lipid amount increased. Drug-excipient compatibility was confirmed by FTIR analysis, while PXRD results showed the disappearance of the sharp peaks found in the pure materials, indicating reduced crystallinity and suggesting that the drug is either in an amorphous form or dispersed in a solid solution state. Conclusion: This study demonstrated successful encapsulation of LX in SLNs, with lipid content controlling the drug release rate. Higher lipid content demonstrated slower drug release.